-26+2d=8(3d-9)

Simple and best practice solution for -26+2d=8(3d-9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -26+2d=8(3d-9) equation:



-26+2d=8(3d-9)
We move all terms to the left:
-26+2d-(8(3d-9))=0
We calculate terms in parentheses: -(8(3d-9)), so:
8(3d-9)
We multiply parentheses
24d-72
Back to the equation:
-(24d-72)
We get rid of parentheses
2d-24d+72-26=0
We add all the numbers together, and all the variables
-22d+46=0
We move all terms containing d to the left, all other terms to the right
-22d=-46
d=-46/-22
d=2+1/11

See similar equations:

| 2x+21+x+3x+4+4x-27=180 | | 4(x-3)=8-5x+6+18+5x+4 | | 3z+5/7=4z+2/7 | | 7.5x-3=1.25x+10.5 | | 6b+30=2(7+5b)= | | -1.5-0.5g=5(3.3g) | | 15=x/7-20 | | R(x)=110x-0.15x^2 | | 2=h/2−1 | | 2=h/2− 1 | | 2=h2− 1 | | 24-3(5t-12)=2-(20t+1) | | -4(1-2n)=24+n | | 3-3(x+3)+4=1 | | 2(8a+3)=21 | | 4x-8+2x+14=180 | | 3+8x-1=x+27+2x | | 3+8x-1=x+27+2 | | (6x+26)+(6x+10)=90 | | Y+-3x=14 | | 7-3s=s-4(2+5) | | 2/3-1/4=2/3(w-1/4) | | Y+13x=-7 | | -12-5n=-3-3(1+n) | | 17x-32+24x=135 | | -8-2(1-9k)=20 | | -12-5n=-3-3(1+;) | | 8b-6=-66 | | -6n-7(2n+1)=-(7n+7) | | 10x-12=9x-9 | | 3x-2=24+6x | | x+.20=55 |

Equations solver categories